Biosynthesis of Novel Ag-Cu Bimetallic Nanoparticles from Leaf Extract of Salvia officinalis and Their Antibacterial Activity - Maqsood Ahmad Malik; Shroog ShdiedRoyji Albeladi; Saleh Mohammed Al-Maaqar; Abdulmohsen Ali Alshehri; Shaeel Ahmed Al-Thabaiti; Imran Khan; Majid Rasool Kamli (Life, 2023)
Bimetallic nanoparticles exhibit bifunctional or synergistic effects prevailing between two metals with the capabilities of enhanced electronic, catalytic, and optical properties. Green synthetic routes have gained tremendous interest because of the noninvolvement of toxic and harmful chemical reagents in preparation. Therefore, we develop bimetallic Ag-Cu nanoparticles (Ag-Cu NPs) through an eco-friendly and biocompatible preparation method. In this study, Ag-Cu NPs have been synthesized from leaf extracts of the commonly known sage, S. officinalis. The extract has a rich phytochemical composition, including bioreducing polyphenols, flavonoids, and capping/stabilizing agents. An array of well-known spectroscopic and microscopic techniques were used to characterize the as-prepared Ag-Cu bimetallic nanoparticles, including X-ray diffraction (XRD), ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The size of the Ag-Cu NPs was found to be 50 nm with a spherical shape and an almost uniform distribution. The antibacterial effect was further evaluated using agar well diffusion and disc diffusion assays. Ag-Cu NPs exhibit antibacterial and antibiofilm properties against Gram-positive and Gram-negative bacteria strains. The minimum inhibitory concentration (MIC) of Ag-Cu NPs was between 5 g/mL and 15 g/mL. The Ag-Cu NPs inhibit biofilm formation at 25 g/mL and 50 g/mL. The results of biogenic Ag-Cu NPs provide novel antibacterial activity against Gram-positive and Gram-negative bacteria, as well as antibiofilm activity. Hence, Ag-Cu NPs might serve as a novel antibacterial agent with potential antibacterial and antibiofilm properties.